Clinical Questions Asked by Long-Term Care Providers Through eConsult: A Retrospective Study. (24th August 2021) - Fung, Celeste; Shah, Soha; Helmer-Smith, Mary; Levi, Cheryl; Keely, Erin; Liddy, Clare
Introduction: eConsult allows primary care providers (PCPs) to access timely specialist advice and informs patient care. To understand the use of eConsult in long-term care (LTC) settings, we examined the clinical content and types of questions asked by LTC PCPs. Methods: A descriptive, retrospective study of eConsults submitted through the Champlain BASE™ eConsult Service between January 1, 2017, and December 31, 2018, by LTC PCPs was conducted. Cases were classified using validated taxonomies. Descriptive statistics were generated for content and question type classifications, service utilization data, and close-out survey responses. Results: 22 LTC PCPs submitted 113 eConsults. They sought advice about drug treatment (58%), diagnosis (44%), and management (38%) in a breadth of clinical areas, often skin-related (39%). Long-term care PCPs frequently asked more than one question type (42%). They received advice within 1 week (91%) and rated eConsult as very helpful and educational. Three case examples are presented. Conclusion: This study demonstrates the type of advice LTC PCPs are seeking through eConsult and its usefulness in this setting. Long-term care stakeholders are encouraged to consider implementing eConsult in other regions, as a means to improve access to timely specialist advice, support clinical decision-making, and improve residents' quality of life.